Re-education as Ethnocide. Beyond the Nazi Concept of “Umvolkung” - Němec, Jiří (Wydawnictwo Uniwersytetu Rzeszowskiego, 2021)
The paper deals with re-education as one of the hidden symbols of modernity using the example of National Socialist nationality politics. It analyses a theoretical concept behind the National Socialist ethnic and racial policy in East Central Europe, especially in the Protectorate of Bohemia and Moravia. It presents the concept of Umvolkung as a theoretical basis on which it was possible to think of a significant part of the Czech population that met the racist criteria of the National Socialists, that it was originally the German population who lost its national identity during the centuries. The concept should also help to develop a strategy to re-educate the people of the Protectorate, and in the long run it should eventually lead to ethnocide, i. e. to disintegrate or directly destroy the Czech collective national identity. One of the key figures in shaping the concept was the young Nazi scholar Hans Joachim Beyer (1908–1971), who came to the Protectorate on the advice of the Deputy Reich Protector Reinhard Heydrich and headed the most politically influenced Science Foundation in Czech Lands (Reinhard Heydrich Foundation for Scientific Research in Prague). In order to justify the future National Socialist Germanization policy, Beyer developed a new theory of the origins of the Czech people in collaboration with the anthropologist K. V. Müller.

Artykuł dotyczy reedukacji jako jednego z ukrytych symboli nowoczesności na przykładzie narodowosocjalistycznej polityki narodowościowej. Analizuje teoretyczną koncepcję polityki etnicznej i rasowej narodowosocjalistycznej w Europie Środkowo-Wschodniej, zwłaszcza w protektoracie Czech i Moraw. Przedstawia koncepcję „Umvolkung” jako teoretyczną podstawę postrzegania znacznej części ludności czeskiej, która spełniała rasistowskie kryteria narodowych socjalistów, jako pierwotnie ludności niemieckiej, która straciła swoją tożsamość narodową w ciągu wieków. Koncepcja ta miała również przyczynić się do opracowania strategii na rzecz reedukacji ludności Protektoratu, a w dłuższej perspektywie ostatecznie doprowadzić do etnocydu, czyli rozpadu lub bezpośredniego zniszczenia czeskiej tożsamości narodowej. Jedną z kluczowych postaci w promowaniu tej koncepcji był młody nazistowski uczony Hans Joachim Beyer (1908–1971), który przybył do Protektoratu za radą Zastępcy Protektora Rzeszy Reinharda Heydricha i stanął na czele najbardziej wpływowej politycznie Fundacji Naukowej na Ziemiach Czeskich (Fundacja Badań Naukowych Reinharda Heydricha w Pradze). Aby uzasadnić przyszłą narodowosocjalstyczną politykę germanizacji, Beyer opracował nową teorię początków narodu czeskiego we współpracy z antropologiem K.V. Müllerem.
Keywords: Protectorate of Bohemia and Moravia; Nazi politics of assimilation; social engineering; racial theory; war science; Reinhard Heydrich Stiftung in Prague; Protektorat Czech i Moraw; nazistowska polityka asymilacji; inżynieria społeczna; teoria rasowa; nauki wojenne; Reinhard Heydrich Stiftung w Pradze